Assessment of extracellular activities of novel microorganisms for biodegradation of palm oil mill effluent (POME) - Alade, Abass O.; Jameel, Ahmad Tariq; Muyibi, Suleyman Aremu; Abdul Karim, Mohamed Ismail; Alam, Md. Zahangir (2012)
Palm oil mill effluent (POME) constitutes 60% of the wastes generated in typical palm oil mill and its environmental impact has been identified to be harmful to aquatic lives. This project examined the potential of degrading POME with microorganisms that are indigenous to POME. Thus, two microorganisms were isolated from POME using serial dilution (10−1 to 10−10) procedure on solid plates containing Potato Dextrose Agar (PDA), Sabouround Dextrose Agar (SDA) and Malt Extract Agar (MEA), respectively. The two microorganisms (TRQ1 and TRQ2) that consistently appeared on the three media plates were quantified and subjected to extracellular enzymatic activities such as amylolytic, gelatinolytic, cellulolytic and lipolytic. The two isolates, TRQ1 and TRQ2, showed negative response to amylolytic test and this confirmed that they are not fungi; however they are Gelatinolytic and Cellulolytic. TRQ1 showed low lipolytic activity while TRQ2 did not show any. The diameter covered by TRQ1 and TRQ2 on gelatin media were 8.5 and 8.0cm respectively, while the spread on cellulose media were 3.5 and 3.25 cm, respectively, on the seventh day. Furthermore, TRQ1 covered a diameter of 1.65cm while TRQ2 retained its initial diameter. These results show that TRQ1 and TRQ2 contain gelatinolytic and cellulolytic enzymes and can be utilized for the degradation of cellulosic substrates present in POME, in particular. The cheap and wide availability of the material (POME) used as source for the production of these microorganisms indicates their economic importance for industrial applications and environmental sustainability, particularly in converting waste to wealth. Keywords: Biodegradation; Cellulolytic; Gelatinolytic; Lipolytic; Microorganisms; POME